1986
DOI: 10.1016/0304-3959(86)90038-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of contemporary MMPI norms in the study of chronic pain patients

Abstract: In a previous study, Ahles et al. [1] compared the MMPI results of primary fibromyalgia, rheumatoid arthritis and non-pain control participants. The purpose of the present study was to reanalyze the original data using the contemporary norms of Colligan et al. [5]. The reanalysis revealed that the pattern of group differences remained the same; however, the number of primary fibromyalgia patients classified as 'psychologically disturbed' was appreciably reduced. These data have clinical relevance in that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…The results of the present study suggest that the chronic pain patients evaluated are not that much different on the MBHI coping styles and psychogenic attitude scales than a non-medical population. This finding is consistent with recent studies that compared personality and psychological characteristics of pain patients to non-medical populations, as well as the few studies reported on the MBHI (Ahles et al, 1986;Bradley et aI., 1981;Elkins & Barret, 1984). However, the differences that were found are consistent with what is known about chronic pain patients, i.e., they are more likely to be depressed and anxious (Elkins & Barret, 1984;Fishbain et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study suggest that the chronic pain patients evaluated are not that much different on the MBHI coping styles and psychogenic attitude scales than a non-medical population. This finding is consistent with recent studies that compared personality and psychological characteristics of pain patients to non-medical populations, as well as the few studies reported on the MBHI (Ahles et al, 1986;Bradley et aI., 1981;Elkins & Barret, 1984). However, the differences that were found are consistent with what is known about chronic pain patients, i.e., they are more likely to be depressed and anxious (Elkins & Barret, 1984;Fishbain et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…When psychological aspects of medical patients are being considered in clinical and research activities, the MMPI is one of the primary psychological assessment procedures that often is included. Research that used the MMPI to compare patients with "organic" vs. "functional/psychogenic" pain (primarily low back pain) has produced inconsistent results and has been plagued with methodological problems (Ahles, Yunus, Gaulier, Riley, & Masi, 1986;Bradley, Prokop, Gentry, Van Der Heidi, & Prieto, 1981;Carlsson, 1986;Elkins & Barrett, 1984).…”
mentioning
confidence: 99%
“…Groups were statistically recalculated to separate a normal (healthy) group, a chronic pain group and a psychologically disturbed group [13, 29, 35]. These studies reported that less than one-third of fibromyalgia patients could be categorized into the psychologically disturbed group with 41% normal and 47% having the chronic pain profile.…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Ahles et al (24), FM patients obtained more elevated scores on 8 MMPI scales, as compared with a matched control group. Thirty-one percent were "psychologically disturbed", whereas 33% showed a typical "pain profile" and 36% obtained "normal" profiles.…”
mentioning
confidence: 92%
“…Fibromyalgia is a controversial diagnosis; arguments have been put forward that FM should not be recognized as an organic syndrome (23). Other authors have considered the existence of "psychological disturbance" in FM (24,25). Psychological factors are proposedly important in the development of FM and the possible contribution of both somatisation mechanisms and depression has been raised.…”
mentioning
confidence: 99%